Path planning and re-planning of lane change manoeuvres in dynamic traffic environments. (17th May 2019) - Norouzi, Armin; Kazemi, Reza; Abbassi, Omid Reza
Automatic lane change is of utmost importance in designing autonomous vehicles and driver assistant systems. In this study, a novel path for lane change manoeuvres, based on mathematical functions, is introduced. To obtain a suitable path for lane change manoeuvres, four functions, namely quintic, septic, sinusoidal, and tangent functions, were examined. The analysis revealed that, according to the ISO Standards and peak acceleration criterion, a quintic function has the advantage of passenger comfort over other path functions. After choosing the appropriate path, an algorithm for re-planning the lane change path, based on dynamic traffic conditions, was proposed. The simulation results show that the proposed algorithm is capable of designing the path in various traffic conditions. Moreover, the algorithm can navigate the vehicle to the initial lane, if the manoeuvre is not possible. Our analytical results showed that the designed paths are suitable, comfortable, and safe.